2016
DOI: 10.5698/1535-7511-16.6.408
|View full text |Cite
|
Sign up to set email alerts
|

Expecting the Unexpected: Lack of in Vivo Network Defects in an Scn1a Model of Dravet Syndrome

Abstract: CommentaryDravet syndrome (DS) is a severe pediatric epileptic encephalopathy with disease onset in the first year of life. Patients have normal presentation before seizure onset and then experience frequent seizures, ataxia, cognitive deficits, and a high risk of sudden unexpected death in epilepsy (1). The majority of DS cases are caused by de novo loss-of-function mutations in SCN1A, encoding the voltage-gated sodium channel Na v 1.1, resulting in haploinsufficiency (2-4).Early studies in Scn1a −/+ mice sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It has also been shown that alterations in interneuronal firing seen in Scn1a +/− DS mice do not alter intrinsic network excitability in vivo (De Stasi et al 2016). According to Hull and Isom (2016), there might be other factors such as pyramidal neuron hypere xcitability that alter the network dynamics during a seizure, and pyramidal neuron function has been shown to be altered in neurons derived from induced pluripotent stem cells from Dravet patients (Liu et al 2013). For these reasons, we investigated the firing properties of pyramidal neurons in the current study, and we found increased excitability in CA3 pyramidal neurons of mutant mice that had undergone A/PFE.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that alterations in interneuronal firing seen in Scn1a +/− DS mice do not alter intrinsic network excitability in vivo (De Stasi et al 2016). According to Hull and Isom (2016), there might be other factors such as pyramidal neuron hypere xcitability that alter the network dynamics during a seizure, and pyramidal neuron function has been shown to be altered in neurons derived from induced pluripotent stem cells from Dravet patients (Liu et al 2013). For these reasons, we investigated the firing properties of pyramidal neurons in the current study, and we found increased excitability in CA3 pyramidal neurons of mutant mice that had undergone A/PFE.…”
Section: Discussionmentioning
confidence: 99%
“…Voltage-gated sodium channels, such as NaV1.1, are heterotrimeric protein complexes consisting of a single large pore-forming a subunit in combination with two much smaller b subunits. 20 The noncovalently linked b1 subunit has been shown to modulate the function of the a subunits by enhancing ion flow through a subunits, and by promoting the trafficking of the a subunits from an intracellular pool to the cell surface. 21 We hypothesized that overexpression of NaVb1 would facilitate the activity of residual sodium channel subunits in Scn1a +/mice and mitigate the DS phenotype.…”
Section: Introductionmentioning
confidence: 99%